Effect of combination tablets containing amlodipine 10 mg and irbesartan 100 mg on blood pressure and cardiovascular risk factors in patients with hypertension - Yagi S; Takashima A; Mitsugi M; Wada T; Hotchi J; Aihara K; Hara T; Ishida M; Fukuda D; Ise T; Yamaguchi K; Tobiume T; et al. (Dove Medical Press, 2015)
Shusuke Yagi,1 Akira Takashima,1 Minoru Mitsugi,2 Toshihiro Wada,2 Junko Hotchi,1 Ken-ichi Aihara,3 Tomoya Hara,1 Masayoshi Ishida,1 Daiju Fukuda,4 Takayuki Ise,1 Koji Yamaguchi,1 Takeshi Tobiume,1 Takashi Iwase,1 Hirotsugu Yamada,1 Takeshi Soeki,1 Tetsuzo Wakatsuki,1 Michio Shimabukuro,4 Masashi Akaike,5 Masataka Sata11Department of Cardiovascular Medicine, Graduate School of Health Biosciences, University of Tokushima, Tokushima, 2Department of Internal Medicine, Shikoku Central Hospital, Shikokuchuo, 3Department of Medicine and Bioregulatory Sciences, 4Department of Cardio-Diabetes Medicine, 5Department of Medical Education, Graduate School of Health Biosciences, University of Tokushima, Tokushima, JapanBackground: Hypertension is one of the major risk factors for cardiovascular and cerebrovascular disease and mortality. Patients who receive insufficient doses of antihypertensive agents or who are poorly adherent to multidrug treatment regimens often fail to achieve adequate blood pressure (BP) control. The aim of this study was to determine the efficacy of an angiotensin II receptor blocker (ARB) and calcium channel blocker (CCB) combination tablet containing a regular dose of irbesartan (100 mg) and a high dose of amlodipine (10 mg) with regard to lowering BP and other risk factors for cardiovascular disease.Methods: We retrospectively evaluated data from 68 patients with essential hypertension whose treatment regimen was changed either from combination treatment with an independent ARB and a low-dose or regular-dose CCB or from a combination tablet of ARB and a low-dose or regular-dose CCB to a combination tablet containing amlodipine 10 mg and irbesartan 100 mg, because of incomplete BP control. Previous treatments did not include irbesartan as the ARB.Results: The combination tablet decreased systolic and diastolic BP. In addition, it significantly decreased serum uric acid, low-density lipoprotein cholesterol, and increased high-density lipoprotein cholesterol levels, independent of the BP-lowering effect. Treatment with the combination tablet did not affect serum triglycerides, plasma glucose, glycated hemoglobin, serum potassium or creatinine levels, or the urinary albumin excretion rate.Conclusion: The combination tablet containing amlodipine 10 mg and irbesartan 100 mg had a greater BP-lowering effect than an ARB and a low-dose or regular-dose CCB. In addition, the combination tablet had more favorable effects on serum uric acid, low-density lipoprotein cholesterol, and high-density lipoprotein cholesterol levels in patients with hypertension.Keywords: blood pressure, combination tablet, uric acid, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol